"That sort of place …where filthy men go …": a qualitative study of women's perceptions of genitourinary medicine services. Issue 5 (1st October 2001) - Scoular, Anne; Duncan, Barbara; Hart, Graham
Abstract : Background: A stigma is a pejorative social label. Stigmatisation is a process by which individuals are made to experience isolation and reduced opportunities in life. Some diseases are particularly associated with stigmatising attitudes; this applies particularly to sexually transmitted infections. Although several studies report the effects of stigma, no study to date has attempted to investigate its nature, which is a prerequisite to designing health interventions. Methods: This qualitative, exploratory study investigated the experience of stigma among young women recently diagnosed with an STI and considered the implications of these experiences in terms of maximising access to GUM clinics. Results: Three themes were identified from interviews undertaken with women recruited in family planning and genitourinary medicine (GUM) clinics: the perception of STIs as a condition of "others, " the threatening nature of the GUM clinic, and the evolution of the experience of stigma within the GUM clinic. Conclusion: More open discussion and education about sexual health services and STIs should take place at a general population level; awareness of sexual health services should be raised in inclusive ways, which are seen as relevant to the needs of a wide range of individuals; medical, nursing, and counselling staff in GUM clinics should be supported in their efforts to reduce the experience of stigma. Finally, future interventions designed to improve access to sexual health services should formally assess their impact on stigma.